The Fundus Autofluorescence Spectrum of Punctate Inner Choroidopathy - Miaoling Li; Xiongze Zhang; Feng Wen (Journal of Ophthalmology)
Purpose. To investigate the fundus autofluorescence (FAF) spectrum of punctate inner choroidopathy (PIC). Methods. This is a retrospective observational case series of 27 consecutive patients with PIC admitted from October 2013 to March 2015, who underwent short-wavelength- (SW-) and near-infrared- (NIR-) FAF imaging, spectral domain optical coherence tomography (SD-OCT), fluorescein angiography (FA), and indocyanine green angiography (ICGA). Results. There were three primary findings on the FAF imaging of patients with PIC. First, active PIC lesions revealed hypoautofluorescent spots with hyperautofluorescent margin. After the lesions regressed, the hyperautoflurescent margin faded. Second, subclinical and most of the atrophic PIC lesions appeared to be hypoautofluorescent spots. But subclinical PIC lesions were more distinctive on NIR-FAF imaging than on SW-FAF imaging. Third, hypoautofluorescent spots of PIC lesions coexisted with hyperautofluorescent patches on SW-FAF imaging. These hyperautofluorescent patches were demonstrated to be multiple evanescent white dot syndrome (MEWDS) or acute zonal occult outer retinopathy (AZOOR) lesions by subsequent multimodal imaging and faded during follow-up examinations. Conclusion. FAF imaging helps in noninvasively tracking the evolution of PIC lesions and identifying the combined MEWDS or AZOOR lesions, complementary to SD-OCT and angiographic studies.